2018
DOI: 10.1007/s11010-018-3484-8
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of PCSK9 gene expression and diminished level of LDL-receptor in rat liver as a potential cause of post-lipectomy hypercholesterolemia

Abstract: Studies designed to examine effects of fat mass reduction (including lipodystrophy and lipectomy) on human serum total and LDL-cholesterol concentrations are inconsistent. The purpose of this study was to examine effect of partial lipectomy in rats (as an experimental model of fat mass reduction in humans) on (1) circulating total cholesterol, LDL-cholesterol + VLDL-cholesterol and HDL-cholesterol concentrations, and (2) factors which may affect serum cholesterol concentrations such as: (a) liver LDL-receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…These histopathological changes in the body were important formative indices of hypercholesterolaemia, with some beneficial changes appearing in the Model-G group, such as improved aortic wall structure and neatly arranged myocardial cells. Lipid deposition has been identified as an important cause of AS, which can lead to the increase of free radicals, thereby damaging endothelial cell function (30)(31)(32). Thus, the release of protective factors is reduced, leading to a reduction in the tightness of endothelial cells and increased permeability, which in turn results in increased lipid deposition, forming a vicious circle (33).…”
Section: Discussionmentioning
confidence: 99%
“…These histopathological changes in the body were important formative indices of hypercholesterolaemia, with some beneficial changes appearing in the Model-G group, such as improved aortic wall structure and neatly arranged myocardial cells. Lipid deposition has been identified as an important cause of AS, which can lead to the increase of free radicals, thereby damaging endothelial cell function (30)(31)(32). Thus, the release of protective factors is reduced, leading to a reduction in the tightness of endothelial cells and increased permeability, which in turn results in increased lipid deposition, forming a vicious circle (33).…”
Section: Discussionmentioning
confidence: 99%
“…This made the SG rats similar to the control group, at least with respect to the PCSK9 protein level. Interestingly, a study by Dettlaff-Pokora et al [34] indicated that a partial surgical removal of adipose tissue (i.e., white adipose tissue (WAT)) in rats may cause an upregulation of liver PCSK9-encoding genes. This probably contributed to an elevated level of circulating PCSK9 and a decrease in the liver LDLR expression.…”
Section: Discussionmentioning
confidence: 99%